Vmh2 hydrophobin as a tool for the development of "self‐immobilizing" enzymes for biosensing. Issue 1 (26th July 2016) - Piscitelli, Alessandra; Pennacchio, Anna; Longobardi, Sara; Velotta, Raffaele; Giardina, Paola
ABSTRACT: Self‐assembling proteins forming amyloid fibrils are promising candidates for the fabrication of biomaterials, due to the chemical and mechanical stability of their structures. Among potential applications, their use as platforms for enzyme immobilization is rapidly gathering attention. In this work, we demonstrate that the production of the enzyme glutathione‐S‐transferase (GST) fused to the class I hydrophobin Vmh2 from Pleurotus ostreatus represents an invaluable tool for the development of self‐immobilizing enzymes useful for high throughput analyses. The proposed immobilization strategy is versatile since it can be applied, in principle, to every recombinant protein able to refold from Escherichia coli inclusion bodies. A GST based biosensor has been developed to quantify toxic compounds, such as the pesticides molinate and captan, in aqueous environmental samples. The main advantages of this sensor include simplicity and speed of preparation, high sensitivity, reusability, and accuracy. Biotechnol. Bioeng. 2017;114: 46–52. © 2016 Wiley Periodicals, Inc. Abstract : A fungal self‐assembling hydrophobin was genetically fused to an active enzyme. The fusion protein was exploited to efficiently and stably functionalize surfaces. A handy and sensitive pesticide biosensor was developed using the hydrophobin‐GST fusion protein tightly bound to a polystyrene multiwell plate.